2022
DOI: 10.3389/froh.2022.871107
|View full text |Cite
|
Sign up to set email alerts
|

Biosafety in Dental Health Care During the COVID-19 Pandemic: A Longitudinal Study

Abstract: BackgroundThe coronavirus disease 2019 (COVID-19) pandemic had quite an impact on dental health care. Concerns about the risk of SARS-CoV-2 transmission through contaminant fluids and droplet formation during several dental procedures highly impacted dental health care, drastically reducing the number of dental practices worldwide. To monitor SARS-CoV-2 contamination in dental clinics, a longitudinal study was carried out during the return of dental practice at university.MethodsDental health care professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Another study published in 2022 assessed the use of biosecurity measures during dental care in preventing COVID-19 infections over a three-month period. The study's results demonstrated that maintaining prevention measures significantly reduced the rates of COVID-19 infection during dental care [ 36 ]. Therefore, the results of the two aforementioned studies, along with the findings of the present study, reinforce the theory that maintaining minimum prevention measures, even after the most severe infection waves of COVID-19 could help prevent new pandemics and avoid potential COVID-19 infection outbreaks [ 37 ], which can arise from the extreme relaxation of prevention measures [ 38 ] or new virus variants that continue to emerge [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study published in 2022 assessed the use of biosecurity measures during dental care in preventing COVID-19 infections over a three-month period. The study's results demonstrated that maintaining prevention measures significantly reduced the rates of COVID-19 infection during dental care [ 36 ]. Therefore, the results of the two aforementioned studies, along with the findings of the present study, reinforce the theory that maintaining minimum prevention measures, even after the most severe infection waves of COVID-19 could help prevent new pandemics and avoid potential COVID-19 infection outbreaks [ 37 ], which can arise from the extreme relaxation of prevention measures [ 38 ] or new virus variants that continue to emerge [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Being the last levels of risk prevention, it is not appropriate to use them as the only protection methods, especially when there are other options to reduce it [ 19 ] Dental practice can be executed safely when adequate control measures and biosecurity protocols are applied, such as the proper use of surface disinfection and PPE, which are essential to avoid cross-infection [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For SARS-CoV-2 RNA detection, RT-PCR assay was performed using saliva samples diluted in viral transport medium, as described previously [ 27 ]. Briefly, viral RNA extraction was executed using the Quick-RNA™ Viral Kit (cat#R1035, ZYMO Research, Irvine, CA USA), and later amplified using the Multiplex Luna ® Universal Probe One-Step RT-PCR Kit (New England Biolabs, Bioscience, Ipswich, MA, USA).…”
Section: Methodsmentioning
confidence: 99%